12=12+(v-8)/2

Simple and best practice solution for 12=12+(v-8)/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=12+(v-8)/2 equation:



12=12+(v-8)/2
We move all terms to the left:
12-(12+(v-8)/2)=0
We multiply all the terms by the denominator
-(12+(v-8)+12*2)=0
We calculate terms in parentheses: -(12+(v-8)+12*2), so:
12+(v-8)+12*2
determiningTheFunctionDomain (v-8)+12+12*2
We add all the numbers together, and all the variables
(v-8)+36
We get rid of parentheses
v-8+36
We add all the numbers together, and all the variables
v+28
Back to the equation:
-(v+28)
We get rid of parentheses
-v-28=0
We add all the numbers together, and all the variables
-1v-28=0
We move all terms containing v to the left, all other terms to the right
-v=28
v=28/-1
v=-28

See similar equations:

| 6^(x-2)=30 | | -v-23=3(v+1)+6 | | -x/2=-20 | | 8^(2x-1)=32 | | -5w=15/4 | | 1.2x=7(x+2.16) | | 2x²-3x+6=0 | | 2(7k-5)+3k=38+5k | | w+7.9=9.64 | | 19=1/2(8x+14) | | v+1=2(4+v) | | u-2.42=1.1 | | 2(4-2x)=7-3x | | 5(y+6)+5y=-30 | | -u+55=223 | | 3/2x-27=24 | | -4(y-3)=3y+47 | | -10+r=5(-8r-2) | | -2=-4+a | | 0.6x=0.8=1.4 | | 171=237-y | | -16r=272 | | -28+8a=-2a+3(4+6a) | | 4(x+4)=10x-20 | | 2b-11=63 | | 60x+40=180 | | -7(8n-7)+5=-5+3n | | Z+37+81+z+40=180 | | 4s-4=8-2s | | 1=y/2-10 | | 2b-11=15 | | k+20=29 |

Equations solver categories